PEMANFAATAN MEDIA SOSIAL SEBAGAI STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN USAHA BUKET BUNGA PADA MAHASISWA - Maratus Shalihah; Rahma Ihda Fatimah Azzahro; Siti Mutmainah; Muhammad Fajrul Falah; Ferida Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The current development of digital technology provides increasing opportunities for Micro, Small, and Medium Enterprises (MSMEs) to reach a wider audience through social media. This study aims to examine how social media is utilized as a marketing strategy to increase sales for a flower bouquet business run by a college student. The research used a qualitative approach with a case study method, with data obtained through in-depth interviews with the owner of Alice Flowers, a flower bouquet business that actively uses Instagram and WhatsApp as its primary means of promotion and communication with customers.The results indicate that social media plays a crucial role in supporting business development. Through digital platforms, entrepreneurs can reach more potential customers, strengthen brand awareness, and increase sales volume. However, several obstacles are encountered, such as limited time to create and manage promotional content, obstacles in shipping orders outside the city, the risk of fraud in online transactions, and intense price competition in the market. Based on these findings, this study concludes that the success of digital marketing for young entrepreneurs, particularly college students, is greatly influenced by the ability to optimize engaging organic content, build partnerships with resellers and relevant communities, and implement effective time management in running and developing the business.